Strategic alliances : formation, implementation, and evolution - Lorange, Peter; Roos, Johan (Cambridge, Mass., USA : Blackwell Business, 1992)
Describing a number of different types of strategic alliances such as joint ventures and project-based co-operation, this work argues that strategic alliances should be a function of the particular strategic intent that a company has.
Includes bibliographical references (p. [280]-284) and index.
oif 26/03/15
Loan
Keywords: International business enterprises -- Case studies; Joint ventures -- Case studies; Strategic alliances (Business) -- Case studies